1997
DOI: 10.1152/jappl.1997.83.5.1432
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide derived from sympathetic nerves regulates airway responsiveness to histamine in guinea pigs

Abstract: Nitric oxide (NO), which can be derived from the nervous system or the epithelium of the airway, may modulate airway responsiveness. We investigated how NO derived from the airway nervous system would affect the airway responsiveness to histamine and acetylcholine in mechanically ventilated guinea pigs. An NO synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME) (1 mmol/kg i.p.) significantly enhanced airway responsiveness to histamine but not to acetylcholine. Its enantiomer D-NAME (1 mmol/kg i.p.), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In human tetraplegic patients, but not low paraplegics, there is reduced baseline airway caliber suggesting that sympathetic interruption could be responsible for the heightened vagomotor airway tone (50). Thus, while these examples support a possible contribution by the SNS, they do not contradict the role of the iNANC system as the principal bronchodilating neural pathway (35) since sympathetic nerves have also been shown to include iNANC fibers (47), the iNANC system is widely distributed in the human airways from the middle trachea to the distal bronchi, and it has been shown to relax cholinergic‐induced contractions (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human tetraplegic patients, but not low paraplegics, there is reduced baseline airway caliber suggesting that sympathetic interruption could be responsible for the heightened vagomotor airway tone (50). Thus, while these examples support a possible contribution by the SNS, they do not contradict the role of the iNANC system as the principal bronchodilating neural pathway (35) since sympathetic nerves have also been shown to include iNANC fibers (47), the iNANC system is widely distributed in the human airways from the middle trachea to the distal bronchi, and it has been shown to relax cholinergic‐induced contractions (7).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is unclear, but in isolated guinea pig trachea, efferent VNS‐induced NANC inhibition (46) was frequency dependent with the maximal inhibition at 32 Hz and similar to our signal. Alternatively, the afferent vagal nerve has been linked with activation of the SNS with either adrenergic nerve (42) or iNANC nerves (47) mediating relaxation in response to histamine. Although the role of smooth muscle SNS innervation on human bronchomotor tone is in question, SNS has been demonstrated in the lungs of most vertebrate species and is known to innervate the human lung such as the pulmonary vasculature (48).…”
Section: Discussionmentioning
confidence: 99%
“…Innervation of the intrathoracic airways is primarily derived from the thoracic sympathetic ganglia. Immunohistochemical analyses and circumstantial evidence gathered in functional studies suggests that a subpopulation of the postganglionic thoracic sympathetic nerves innervating the airways are non‐adrenergic, utilizing the peptide vasoactive intestinal peptide (VIP and related peptides) and/or the gaseous transmitter nitric oxide (NO, synthesized from arginine by the neuronal isoform of NO synthase) to relax airway smooth muscle (Bowden & Gibbins, 1992; Fischer et al 1996; Matsumoto et al 1997). In our pharmacological analyses, we found little evidence for a prominent non‐adrenergic component of the sympathetic response in the trachea, as propranolol reduced the nerve‐mediated relaxations (evoked electrically or reflexively) by an average of >95%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies applying NOS inhibitors have demonstrated a significant decrease in cochlear blood flow following inhibitor application (Brechtelsbauer et al, 1994). Recent evidence indicates that NOS and NADPH-diaphorase are present in a subset of postganglionic sympathetic fibers in locations throughout the body (Fischer et al, 1996;Davisson et al, 1997;Matsumoto et al, 1997;Vials et al, 1997). Thus, the sympathetic innervation of the cochlea may act as one source of NO that mediates blood flow and vascular tone during early stages of the cochlear development.…”
Section: Nadph-diaphorase Label Suggests a Role For No In The Perivasmentioning
confidence: 99%